Relative validity of a short food frequency questionnaire assessing adherence to the Norwegian dietary guidelines among colorectal cancer patients - Henriksen, Hege Berg (Food Nutr Res, 2018)
BACKGROUND: The Norwegian food-based dietary guidelines (FBDG) aim at reducing the risk of developing chronic diseases and promote overall health. We studied the effect of the Norwegian FBDG in colorectal cancer (CRC) patients. There is a need for a time-efficient dietary assessment tool measuring adherence to these guidelines in patients treated for dietary dependent cancer, such as CRC patients. OBJECTIVE: To evaluate a new short food frequency questionnaire (NORDIET-FFQ), developed to estimate adherence to the Norwegian FBDG among CRC patients. DESIGN: Eighty-one CRC patients from both study groups in the Norwegian Dietary Guidelines and Colorectal Cancer Survival study, an ongoing dietary intervention, completed both the short 63-item NORDIET-FFQ and a 7-day weighed food record. RESULTS: The NORDIET-FFQ was on group level able to estimate intakes of fruits, vegetables, unsalted nuts, fish, fatty fish, high fat dairy products, unprocessed meat, processed meat, red meat, water, sugar-rich beverages, alcoholic drinks, and sugar- and fat-rich foods. Ranking of individuals according to intake was good (r = 0.31–0.74) for fruits and vegetables, fruits, unsalted nuts, whole grain products, sugar-rich cereals, fish, fatty fish, dairy products, red meat, water, sugar-rich beverages, alcoholic beverages, and sugar- and fat-rich foods. The NORDIET-FFQ was able to identify the individuals who did not fulfil the recommendations of fruits, vegetables, unsalted nuts, whole grains, low-fat dairy products, processed meat, water, alcoholic beverages, and sugar- and fat-rich foods (sensitivity: 67–93%). CONCLUSIONS: The NORDIET-FFQ showed good ability in to estimate intakes of plant-based foods, fish, dairy products, meat, and energy-dense foods; adequate ranking of individuals according to intake of most recommendations except for unprocessed meat, processed meat, and vegetables; and importantly a good ability to identify those patients in need of dietary counselling for foods that are known to modulate the risk of CRC. TRIAL REGISTRATION: National Institutes of Health ClinicalTrials.gov; Identifier: NCT01570010.